Outcomes Following Repair of Radial, Mid-Body Tears of the Lateral Meniscus in Adolescents: Original Research - Richard Danilkowicz; Kelms Amoo-Achampong; Lucy Meyer; Hinton, Zoe; Lemmex, Devin; Emily Reinke; Alison Toth (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Radial tears of the lateral meniscus result in increased contact forces and expedite arthritis. Due to the technically difficult repair and poor healing, partial or complete lateral meniscectomy is often performed, even in the young, active patient. There is a surprising paucity of literature regarding clinical outcomes after repair of radial tears of the lateral meniscus. This study aims to evaluate a cohort of adolescent patients who have undergone repair of radial tears of the lateral meniscus body at least 2 years after surgery. Methods: With IRB approval, subjects under the age of 18 who underwent repair of mid-body, lateral meniscus tears were identified at least 2 years out from surgery. Of the 18, eight patients completed patient reported outcome surveys. Results: PROs were collected at mean 55.8 months. Mean 2-year IKDC score was 91.67 ± 10.72, and the mean MARX score was 11.63 ± 3.25. Six of eight (75%) reported performance at same level of sport with one reporting pain during sport. Three respondents of the SPORTS score reported continued participation in organized sport, with one patient participating at the collegiate level. Six knees (33%) had postoperative MRI at mean 14 months postop, with five of the six (83.3%) suggestive of preserved integrity of repair. There were five (27.8%) complications, all requiring subsequent surgical procedures. Four patients had meniscus tears at locations distinct from initial injury requiring partial meniscectomies at mean 13.8 months (range, 7-35 months); however, all radial mid-body tears from index procedures were completely healed under arthroscopic visualization. Conclusions: Repairs of radial mid-body tears in the lateral meniscus may provide a significant benefit in the adolescent population. The majority of patients were able to return to their prior activity levels without complication, with evidence of healing on repeat evaluation.